DEPENDENCE OF POWER PROCESSING TIME TO YIELDING X40CrMoV5-1 STEEL THROUGH COMPLEX EROSION BY INTRODUCING THE ELECTROLYTE THROUGH THE TRANSFER OBJECT - Alin NIOATA; Florin CIOFU (Fiabilitate şi Durabilitate)
The processing time represents the duration of the process of processing and one of the indicatives which characterizes the productivity of processing. In this paper, in order to establish the mathematic pattern of the dependence between the processing time and induced power within the workspace tp=f(P) polynomial functions of the 1st, 2nd or 3rd degrees and exponential functions.